EFFECT OF PARTIAL REPLACEMENT OF CEMENT WITH EGGSHELL ASH ADMIXED WITH PLASTIMENT BV-40 IN CONCRETE (FUDMA JOURNAL OF SCIENCES, 2020)
The use of eggshells ash for partial cement replacement in concrete has been well established in earlier studies.The effect of such partial replacement of cement with an eggshell ash admixed with Plastiment BV-40 was investigated in this paper.Tests including slump test, compressive strength test, splitting tensile strength test and concrete density test were carried out on concrete in which cement was partially replaced with 0%, 5%, 10%, 15%, 20% and 25%   eggshell ash admixed with Plastiment BV-40 and presented. The test results indicate that eggshell ash decreases the workability of concrete. Also, for the compressive strength there was an improved maximum compressive strength at 5% ash content, after which there is a decrease in the compressive strength with increase in the ash content. Furthermore, eggshell ash is found to increase the concrete splitting tensile strength. It was concluded that eggshell ash has the potential of being utilized in concrete as partial replacement of cement.
Keywords: Eggshell ash, concrete, partial replacement, slump, setting times, density, compressive and splitting tensile strengths.